Factors contributing to readmission of congestive heart failure patients admitted in internal ward of Hospitals of Shahid Beheshti University of Medical Sciences in Tehran - Ashktorab, Tahereh; Bathaei, sayed ahmad; Zohari Anbuhi, Sima; Alavi Majd, Hamid; Ezati, Jhaleh (Advances in Nursing & Midwifery, 2012)
Factors contributing to readmission of congestive heart failure patients admitted in internal ward of Hospitals of Shahid Beheshti University of Medical Sciences in Tehran Ashktorab, T.1*(PhD); Bathaei, S A.2 (MSN); Zohari Anbuhi, S.3 (MSN); Alavi Majd, H.4 (PhD); Ezati, J.5 (MSN) 1. Associate Professor, Dept. of Medical-Surgical, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Tehran. Iran 2. Alumnus, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Tehran. Iran. 3. Lecturer, Dept. of Medical-Surgical, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Tehran. Iran. 4. Associate Professor, , Dept. of Biostatistics, Faculty of Paramedical, Shahid Beheshti University of Medical Sciences. Tehran. Iran. 5. Lecturer, Dept. of Medical-Surgical, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Tehran. Iran. Abstract Background and aim The prevalence of congestive heart failure (CHF) continues to rise and nearly 5 million people in the United States have CHF, with more than one-half million new cases diagnosed each year. The readmission rate within 3-6 months after discharge in these patients is 10-50 percent. The aim of this study was to determine factors contributing to readmission of patients with congestive heart failure (class 2 and 3) who were admitted in internal ward of Hospitals of Shahid Beheshti University of Medical Sciences in Tehran 2009. Materials and methods In this correlation -descriptive study, 110 patients with congestive heart failure based on 2 and 3 New York Heart Association Classification (NYHA) were included. Subjects were selected by quota purposive sampling and were divided into two groups (readmission and no readmission). Data were collected by a questionnaire. Content validity of the questionnaire was assessed by 10 nursing experts, 5 persons with congestive heart failure and 2 cardiologists. Reliability was measured by ted-retest (0/86). Data were analyzed by SPSS 15. Findings Results showed that, % 61.8 of samples was readmitted to the hospital during the previous 6 months period. In addition, two individual factors (age and literacy level) and two disease related factors (NYHA class and having other disease) contributed to readmissions. Therefore, age and higher NYHA class and having co morbidities had direct and also literacy level indirect relationship with readmissions. Conclusion The readmission rate of patients with congestive heart failure in this study was high. Therefore, attention to contributing factors is needed. Keywords: Congestive heart failure, Readmission, Factors. *Corresponding Author: Dr Ashktorab; Assistant Professor, Dept. of Medical-Surgical, Faculty of Nursing and Midwifery, Shaheed Beheshti Medical University, Shariati, Tehran, Iran. E-mail: t_ashktorab@sbmu.ac.ir